ChemInform Abstract: All‐Carbon N‐Heterocyclic Carbene‐Catalyzed [3 + 2] Annulation Using Donor—Acceptor Cyclopropanes. Issue 36 (August 2016) - Candish, Lisa; Gillard, Rachel M.; Fernando, Jared E. M.; Levens, Alison; Lupton, David W.
Abstract: Review: [24 refs.